Estimation of progression of pediatric myopia in school going children among 4-15 years of age - Ali, Jamshed; Siddiqui, Daud Hasan; Gupta, Sunil Kumar; Mahmood, Wasif; Abbas, Malika; Nisar, Mir Masooma; Zehra, Adeeba; Khan, Salal (International Journal of Research in Medical Sciences, 2025)
Background: Pediatric myopia, or nearsightedness in children, has become a growing public health problem in globally. The increasing prevalence, in rural populations, because lack of eye awareness and, is linked to lifestyle changes such as increased screen time, not proper maintain hygienic condition and reduced outdoor activity. Methods: A prospective study was conducted among 350 school going children aged 4-15 years attending the primary school in rural area. Comprehensive ophthalmic examinations and binocular vision assessment including subjective refraction were performed. Demographic data and family history were collected using structured questionnaires. Results: A total of 350 students of primary school Chandikhera were assessed for this study. Of those 57 students come under these criteria (Pediatric myopia). Of these patients, 61% of patients were male, while 39% female. Overall, 16.28% of total patients had pediatric myopia. The prevalence of myopia increased by the time of 6 months (March to August 2023) from 16.28% to 22.85% (57-80 pediatric myopia patients) in which male pediatric myopic increment about 11.14% to 14.28%, (39-50 male) while in female about 5.14% to 8.57% (18-30 female). Conclusions: The study found a significant association between lack of eye education, increased screen time, not proper diet maintain and higher myopia prevalence in children. Early detection and lifestyle modification are crucial for pediatric myopia control. Promoting outdoor activities, regular eye checkup, maintain diet and hygienic condition and important eye awareness may help reduce progression in pediatric myopia populations especially in rural area.